(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the processes of social adaptation of adolescents, their psychological factors and pedagogical conditions. The study examines the influence of the social environment, family, school and peer group on the formation of the adolescent personality. It also substantiates the effectiveness of socio-pedagogical strategies, approaches in combination with the development of communicative competence and spiritual and moral education in ensuring social adaptation.